Process Mining Techniques in Business Environments Theoretical Aspects, Algorithms, Techniques and Open Challenges in Process Mining - Burattin, Andrea (Lecture Notes in Business Information Processing, 2015)
After a brief presentation of the state of the art of process-mining techniques, Andrea Burratin proposes different scenarios for the deployment of process-mining projects, and in particular a characterization of companies in terms of their process awareness. The approaches proposed in this book belong to two different computational paradigms: first to classic "batch process mining," and second to more recent "online process mining." The book encompasses a revised version of the author's PhD thesis, which won the "Best Process Mining Dissertation Award" in 2014, awarded by the IEEE Task Force on Process Mining.